Strategi Komunikasi Digital Virtual Assistant Course dalam Meningkatkan Kesiapan Kerja di Era Digital - Cholen Lathining Sekar Chandra; Hudi Santoso (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The rise of remote work in the digital era has positioned Virtual Assistant (VA) roles as attractive alternatives for individuals seeking global employment opportunities without the need to migrate. This study explores how digital communication strategies used in VA training courses influence participants' job readiness. The research applies McQuail’s five media functions: Information, Correlation, Continuity, Entertainment, and Mobilization as the framework for analyzing communication strategy. Job readiness is examined through the Employability Theory, focusing on three dimensions: Career Identity, Personal Adaptability, and Social and Human Capital. A quantitative descriptive method was employed by distributing online questionnaires to participants of a Virtual Assistant course. The findings show that media-based communication strategies contribute significantly to learners' readiness to work in digital environments. These strategies enhance engagement, improve message clarity, and increase the relevance of learning materials. The results suggest that well-structured digital communication within VA courses plays an important role in building participants’ employability and global competitiveness. This study provides practical insights for online training providers to strengthen communication practices that support workforce development in a technology-driven world.